New Small Firms and Dimensions of Economic Performance. (February 2015) - Shaffer, Sherrill; Hasan, Iftekhar; Zhou, Mingming
Using data from metropolitan U.S. labor market areas, the authors quantify empirical associations between entry by small firms and multiple economic outcomes including levels, growth rates, and volatilities of income and employment. The inclusion of volatilities, motivated by prior studies, fills an important gap in the empirical analysis of the economic effects of small business entry. We introduce a new measure of excess volatility to reduce any bias from endogeneity or reverse causality. Several robust associations emerge, suggesting a richer variety of effects of entry than previously documented, and raising important new questions for future research and public policy.